Diurnal and inter-annual variability of surface ozone in Baicheng region, China. Issue 1 (1st January 2021) - Qin, Tingting; Wang, Ju; Li, Ran; Fang, Chunsheng
Abstract: With the rapid development of industry and economy, the problem of ozone (O3 ) pollution in China is of increasing concern in recent years. The problem of ozone pollution has become worse in Baicheng City which belongs to the province of Jilin. We analyze the spatial and temporal distribution of surface ozone and its correlation with precursors and meteorological factors during 2015 and 2019 using data from the automatic Atmospheric Environmental Quality Monitoring Station located in Baicheng. Results showed that the daily and monthly mean values of O3 concentration were both single-peak patterns, and interannual variation presented a inverted 'V' pattern in Baicheng. The high concentration of O3 in a year generally occurs from May to July, with the highest daily concentration occurring in the afternoon. The total number of days with O3 concentration exceeding the limits was 35 days from 2015 to 2019, among which the number of days exceeding the maximal daily average eight-hour (MDA8) O3 of 100 μg/m 3 was the highest in 2018, and the 90th percentile MDA8 showed an overall growth pattern. Seasonal variations in O3 concentration in 2018 and 2019 were not consistent with the three previous years.